UJI AKTIVITAS ANTIBAKTERI FORMULASI GEL UNTUK SARIAWAN DARI EKSTRAK DAUN SAGA ( Abrus precatorius Linn. ) TERHADAP BAKTERI Staphylococcus aureus - Ratih Dyah Pertiwi; Joni Kristanto; Graha Ayu Praptiwi (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
One of plants used by Indonesian people as a traditional medicine is saga plant (Abrus precatorius L.). This plant has medicinal properties as medication for thrush, cough and laryngitis. Chemical constituents contained in sage leaves which work as antibacterial are flavonoid and saponin. This study aims to determine the optimal concentration of saga leaves extract which can be formulated in a gel dosage form with qualified physical evaluation and has antibacterial activity against Staphylococcus aureus. Saga leaves extract is prepared by maceration method using ethanol 70% as solvent, and then the extract obtained is preliminarily tested to see its antibacterial activity against Staphylococcus aureus with agar diffusion method. Gel formulation for thrush is made with dispersion method in three formulas with variants of active substance concentration that is FI (1%), FII (3%) and FIII (5%). Gel preparation antibacterial activity test is conducted with agar diffusion method as a plate cylinder. Based on this research, it was found that the extract of saga leaves which is positively made is efficacious as antibacterial and can be formulated into a gel preparation for thrush with optimal concentration in F III (5%), this is indicated by widest diameter of the inhibition area against Staphylococus aureus bacteria